Bird Origins Anew by Alan Feduccia in The Auk, 130(1), January 2013 - Bauer, Henry (Journal of Scientific Exploration, 2013)
In Dogmatism in Science and Medicine (Bauer 2012), I mention a number of fields in which the mainstream position is dogmatic to the nth degree and constitutes a monopoly. That is accompanied by suppression of other views: Dissenters are excluded from conferences, from publishing in leading journals, and from funding of research, and they are labeled “denialists,” with pejorative association to those who deny the Holocaust (Furedi 2007). To the already long list of fields mentioned in the book, I can add the dogma described in this article, that birds are derived in a particular way from a particular line of dinosaurs. The circumstances are uncannily similar to those facing minority views concerning string theory, extinction of dinosaurs, HIV/AIDS theory, the hypothesis of human-caused global warming, etc.: "The current mantra . . . has become an unchallengeable orthodoxy: Birds are living maniraptoran theropods. . . . Those who offer contrary evidence are subjects of ridicule and no longer considered scientists. . . . Only supporting evidence will be recognized, while contradictory evidence is ignored or explained away. . . . All conclusions are based on the fact that “birds are living dinosaurs”. . . . Lack of citation has become a common but disturbing mechanism of censorship. . . . The current orthodoxy of flight origins, involving massive exaptation, stretches biological credulity and is practically non-Darwinian."